Current Issues of the Development of Employee Intercultural Competency in a Work Environment (a case-study of small municipalities of Lithuania) - Gražulis, Vladimiras; Markuckienė, Elžbieta (Socialiniai tyrimai, 2014)
Due to increasing migration, the development of intercultural competency has become more important in the work environment of organizations. Recently, interest in the topic of interculturalism among scientists has increased significantly - there is no doubt that employees of international organizations need to acquire intercultural competency, but this competency of employees in small municipalities of Lithuania has not been studied yet. This study relies on a designed questionnaire which provides for the evaluation of the intercultural competency of employees of small municipalities, as well as the need for its development, and the evaluation of their opinion on the impact of intercultural competency on their career.
Keywords: Management of cultural diversity; intercultural competency; immigration; multiculturalism